Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Konsumen GoFood PT GoTo - Desfitriady; Alivia, Alna Nur; Putri, Evilia Tri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to analyze the impact of service quality and price on customer satisfaction of GoFood PT GoTo. The method used is a quantitative approach with descriptive and associative research design. Data were collected through questionnaires distributed to 112 respondents who are users of the GoFood application. The results of the study show that service quality and price have a significant impact on customer satisfaction. Multiple linear regression analysis indicates that the two independent variables, service quality and price, together contribute significantly to customer satisfaction. This study provides recommendations to improve service quality and adjust prices to be more affordable, to effectively and efficiently increase customer satisfaction.